Using QR Codes to Enhance the Personalized System of Instruction: Column Editor: K. Andrew R. Richards. (2nd January 2018) - Baxter, Deborah; McEntyre, Kelsey; Woodruff, Elizabeth A.
Abstract : The purpose of this article is to propose utilizing quick response (QR) codes, which store and transmit data using the camera on a tablet or smartphone, into personalized system of instruction learning modules.